Firm-level evidence on international stock market movement - Robin Brooks; Marco Del Negro (Federal Reserve Bank of Atlanta, 2003)
We explore the link between international stock market comovement and the degree to which firms operate globally. Using stock returns and balance sheet data for companies in twenty countries, we estimate a factor model that decomposes stock returns into global, country- and industry-specific shocks. We find a large and highly significant link: a firm raising its international sales by 10 percent raises the exposure of its stock return to global shocks by 2 percent and reduces its exposure to country-specific shocks by 1.5 percent. This link has grown stronger over time since the mid-1980s.
Keywords: 330; Financial markets; International finance; Risk